สภาพการอยู่อาศัยของผู้สูงอายุชาวญี่ปุ่นในสถานที่พักเพื่อการท่องเที่ยวพำนักระยะยาว : กรณีศึกษาโครงการริเออิ ลุมพินี เรสซิเดนซ์ กรุงเทพมหานคร - ภาธินี ศรีอาจ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Since the economic crisis in 1997, Thailand has had to face various economic problems resulting in termination of employment. Various ideas have been raised to solve these problems by attracting foreign currency. One of the interesting ideas is making Thailand a center of elderly care in the world to generate income in the country. The Riei Lumpini Residence is one of the projects to accommodate elderly Japanese. The purpose of the study was to investigate the physical characteristics of the residence and the living behaviors of the Japanese elderly to determine their compatibility. The findings indicated that the residents, especially the Japanese, had a need to reside in Thailand for various purposes including physical rehabilitation, tourism, and living in a foreign country with a lower cost of living. These elderly may live with their expatriate children or live alone using the healthcare services of the Riei Company. Data was collected during the period of time between September 2006 and February 2007. The study findings should shed light on the needs of long-stay residents in the future, that a guideline for the improvement of activities and space utilization to best serve the needs of the residents and hence to increase their quality of life in Thailand. They chose Thailand because of the low costs of living, the availability of healthcare services. As for the sources of their spending money, most financial support came from their savings and pensions. Moreover, there were some residents who continued to work after retirement such as running their own business or teaching the Japanese language to Thai people. Thus, they were able to earn a steady monthly income. Favorite activities in the residence were using the sauna and fitness club. They also liked to take a nap and they enjoyed festivities and cultural activities organized in the residence. In terms of the needs of residents, it was discovered that they needed a residence in the community with proximity to a hospital and transportation. They also wanted a garden in dwelling place or near a community park for relaxation, a living room for neighbor and a Japanese-styled rock spa. The problems they had when they went out were communication problems, a lack of knowledge about how to get around Bangkok, and food-related. Finally, what they wanted to see improved was the size of the bathroom which was too small for a wheelchair and lacked the standard equipment required by the elderly residents. Based on findings, the common space should suit the living behaviors of the residents, and the space in the unit should be improved to meet living standards and to satisfy the needs of the residents. Finally, this type of project should be located in an area where there are a lot of Japanese residents, shopping centers for Japanese products, and ease of transportation.